2010
DOI: 10.1016/j.jclinepi.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Decreased accuracy in interpretation of community-based screening mammography for women with multiple clinical risk factors

Abstract: Objective To assess the impact of women's breast cancer risk factors (use of hormone therapy, family history of breast cancer, previous breast biopsy) on radiologists' mammographic interpretive performance and whether the influence of risk factors varies according to radiologist characteristics. Study Design and Setting Screening mammograms (n=638,947) performed from 1996 to 2005 by 134 radiologists from three Breast Cancer Surveillance Consortium registries were linked to cancer outcomes, radiologist survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…Positive associations between FP recall and previous breast biopsies, family history of breast cancer, postmenopausal hormone therapy use, more recent exam year, and time between screening exams have been reported previously, as have negative associations between FP recall and older age and comparison film availability (6,15,18,(27)(28)(29). We also identified statistically significant associations between FP recall and family history of breast cancer, exam year, time since previous mammogram, and availability of comparison films.…”
Section: Discussionsupporting
confidence: 84%
“…Positive associations between FP recall and previous breast biopsies, family history of breast cancer, postmenopausal hormone therapy use, more recent exam year, and time between screening exams have been reported previously, as have negative associations between FP recall and older age and comparison film availability (6,15,18,(27)(28)(29). We also identified statistically significant associations between FP recall and family history of breast cancer, exam year, time since previous mammogram, and availability of comparison films.…”
Section: Discussionsupporting
confidence: 84%
“…Interpretive performance of screening mammography is known to vary by patient (4, 2325), radiologist (47, 9, 11, 2430) , and facility level characteristics. (30, 31) However, the extent to which screening mammography performance varies by the radiologic technologist has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…(4, 23, 24) Radiologist level factors found to affect performance include time since graduation from residency, breast-imaging fellowship/training, annual interpretative volume, years of mammographic imaging and interpretation, and primary affiliation with an academic medical center. (47, 9, 2426, 2830) Facility level characteristics that may affect performance include volume, screening versus diagnostic mammography mix, having breast imaging specialists interpreting the examinations, and having audits two or more times per year. (30, 31) Despite numerous studies examining the patient, radiologist, and facility characteristics, variation in performance measures still exist and perhaps it is due to the radiologic technologist obtaining the image.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that mammography sensitivity is lower in dense breasts compared to fatty breasts [9][10][11][12][13][14][15][16][17][18][19]. Cook et al [17] reported that the sensitivity of mammography for women with extremely dense breasts was as low as 29 %, whereas recall rates among them increased by 17 % compared to in scattered fibroglandular dense breasts. To compensate for decreased performance of mammography in women with denser breasts, several studies using complemental imaging modalities have been reported.…”
Section: Influence Of Breast Density On Breast Cancer Screening Breasmentioning
confidence: 99%